Using Perceived Landscape Benefits to Promote Water Conservation Behaviors in Urban Areas - Amanda D. Ali; Laura A. Sanagorski Warner; Anil Kumar Chaudhary (EDIS, 2018)
Because a large percentage of water used in urban areas can be applied through irrigation, home landscape management practices are an important factor of water conservation. The information in this 5-page document is the result of a cluster analysis used to identify meaningful subgroups among home irrigation users to encourage water conservation behaviors. Written by Amanda D. Ali, Laura A. Sanagorski Warner, and Anil Kumar Chaudhary and published by the UF/IFAS Department of Agricultural Education and Communication, May 2018. http://edis.ifas.ufl.edu/wc291